Influence of different racing positions on mechanical and electromyographic patterns during pedalling - Dorel, S.; Couturier, A.; Hug, F. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The aim of this study was to test the hypothesis that, in comparison with standard postures, aero posture (AP) would modify the coordination of lower limb muscles during pedalling and consequently would influence the pedal force production. Twelve triathletes were asked to pedal at an intensity near the ventilatory threshold (VT+?20%) and at an intenisty corresponding to the respiratory compensation point (RCP). For each intensity, subjects were tested under three positions: (1) upright posture (UP), (2) dropped posture (DP), and (3) AP. Gas exchanges, surface electromyography and pedal effective force were continuously recorded. No significant difference was found for the gas-exchange variables among the three positions. Data illustrate a significant increase [gluteus maximus (GMax), vastus medialis (VM)] and decrease [rectus femoris (RF)] in electromyography (EMG) activity level in AP compared with UP at RCP. A significant shift forward of the EMG patterns (i.e. later onset of activation) was observed for RF (at VT+Delta20% and RCP), GMax, VL, and VM (at RCP) in AP compared with UP. These EMG changes are closely related to alteration of force profile in AP (higher downstroke positive peak force, lower upstroke negative peak force, and later occurrence of these peaks along the crank cycle).